1
$\begingroup$

So using the quadratic formula to give the solution for $x$ (in terms of $p$) for:

$$px^2+2x+1=0$$

which as far as i've figured out gives:

$$x = \frac{-2\pm\sqrt{4-4p}}{2p}$$

but i don't know how to find the values of $p$ that make this equation have real solutions for $x$.

$\endgroup$
  • 2
    $\begingroup$ Complete the square. Or consider the sign of the discriminant. If nothing works, please post back your attempts and where you got stuck. $\endgroup$ – dxiv Feb 5 '18 at 6:27
  • 2
    $\begingroup$ What could make the number in your formula non-real? $\endgroup$ – Jyrki Lahtonen Feb 5 '18 at 6:34
  • $\begingroup$ Hint: We cannot divide by $0$, so $2p\neq 0$ and therefore $p\neq 0$. We now have that $p\gtrless 0$ but if $p > 0$ then $4 - 4p < 0$. $\endgroup$ – Feeds Feb 5 '18 at 6:52
2
$\begingroup$

It has a real solution if the term inside the square root is nonnegative, that is $$4-4p \geq 0$$

$$4\geq 4p$$

Divided by $4$, we have

$$1 \geq p$$

Note that $4-4p$ the term inside the square root, is also known as the discriminant.

Remark:

Consider the case when $p=0$ separately, in that case, the equation is a linear equation.

$\endgroup$
1
$\begingroup$

The $Δ$(the discriminant of a quadratic) of the quadratic must be non negative for the quadratic to have real solutions. In your case $$Δ=4-4p$$ Hence $$4-4p\ge 0$$ $$\Rightarrow p-1\le 0$$ $$\Rightarrow p\le 1$$

$\endgroup$
0
$\begingroup$

We have, $$x = \frac{-2\pm\sqrt{4-4p}}{2p} = \frac{-1\pm \sqrt{1-p}}{p}.$$ Since $p\in\mathbb{R}$ then $\sqrt{-1}\nmid p$ and therefore $p\not>1\Leftrightarrow p\leqslant 1$ since if on the other hand, $p > 0$, then $1 - p < 0$ and therefore $\sqrt{-1}\mid \sqrt{1 - p}$. In addition to that, $-1 = \sqrt{-1}^2$ thus the entire numerator is a multiple of $\sqrt{-1}$. This means that $\sqrt{-1}\mid px$, proving the claim that $p\leqslant 1$. Of course though, we also cannot divide by $0$, therefore $p< 0$.

This is why that for any $x\in\mathbb{R}$, if $ax^2 + bx + c = 0$ then the expression under the root in the quadratic formula, $$x = \frac{-b\pm\sqrt{b^2 - 4ac}}{2a},$$ namely $(b^2 - 4ac)$, must be non-negative since $-b = b\sqrt{-1}^2$, therefore $b^2 - 4ac\geqslant 0\Leftrightarrow 4ac \geqslant b^2$.

In clearing up a potential misunderstanding:

I say that $p < 0$, but if $p=0$ then $\exists x \in \left\{\mathbb{R} : px^2 + 2x + 1 = 0\right\}\Leftrightarrow x = -\dfrac 12$. Although this is true, this implies that, $$px^2 + 2x + 1 = 0\Leftrightarrow 2x + 1 = 0,$$ which is why $x = -\dfrac 12$ however if $p = 0$ then the above equation is not a quadratic trinomial to begin with.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.